A Systematic Review of the Clinical Manifestations and Diagnostic Methods for Macular Coloboma. (3rd July 2021) - Hou, Xiaoyi; Guo, Yongwei; Liu, Jinhua; Li, Senmao; Fan, Wanlin; Lin, Ming; Rokohl, Alexander C.; Heindl, Ludwig M.
ABSTRACT: Objectives : To present the clinical features of and diagnostic methods used for macular coloboma (MC), and to analyze the factors associated with best-corrected visual acuity (BCVA) in patients with MC. Methods : A systematic review using the MEDLINE (PubMed), EMBASE, LILACS, and Cochrane databases was performed. The factors associated with BCVA were analyzed. Results : A total of 21 patients (mean age at diagnosis, 18.1 ± 14.6 years) with 36 eyes affected by MC (5 unilateral, 16 bilateral) were included in the study. All 21 patients (100%) had undergone a good-quality fundus examination. The size of the MC lesions ranged from 1.0 × 1.2 to 4.0 × 4.0 disc diameters (DD). Twenty-seven (73%) eyes had pigmented MC, seven (19%) had non-pigmented MC, and one (3%) had an unspecific type. The diagnosis was confirmed using spectral-domain optical coherence tomography (SD-OCT) in 16 (43.2%) eyes. A positive correlation was found between BCVA and the type of MC (β = 0.876, p = .006) and abnormal eye movement (β = 0.087, p = .018), and a negative correlation was found between BCVA and a contributory medical history of ventricular septal defect (β = −0.327, p = .001). Conclusions : Pigmented MC was the most common type and had the highest possibility of causing impaired vision in the affected eyes. Additionally, joint examinations should be applied for diagnostic confirmation of MC. Furthermore, fundoscopy, electroretinogram, electrooculography, fundus fluorescein angiography, and SD-OCT are all critical for differential diagnosis of MC-like lesions.